(untitled) - Schaller, Michael (New York, 1985)
This book provides a novel perspective on the origins of the Cold war in Asia, tracing it all the way back to the occupation of Japan after World War II
Keywords: United states,Japan; Foreign relations,Foreign relations; Japan,United states